2020
DOI: 10.1111/jfpp.14686
|View full text |Cite
|
Sign up to set email alerts
|

Improving the resistant starch in succinate anhydride‐modified cardaba banana starch: A chemometrics approach

Abstract: Resistant starch of succinate anhydride‐modified cardaba banana starch was model using response surface methodology (RSM) and artificial neural network (ANN). This was investigated by varying the octenyl succinic anhydride (OSA) concentration (3%–5%), time (30–60 min), and pH (8–10) using a Box–Behnken design. According to the result, both the RSM and ANN modeling techniques predict the modification process with high accuracy (coefficient of determinant, R2 > .97 and root mean square of error =.44–.47). The op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…After all, when starch is broken down, it is reduced to glucose, which is in the form of sugar, supplying sugar to the blood. Therefore, eating a high quantity of starch results in a high level of glucose in the human blood, however, in the case of consuming resistant starch which is immune to digestion, there is a reduction in the glucose in the blood because the starch is not broken dow thereby reducing the risks of some blood diseases that might arise due to excess glucose in the blood ( Olawoye et al., 2020b ).…”
Section: Classification Of Polysaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…After all, when starch is broken down, it is reduced to glucose, which is in the form of sugar, supplying sugar to the blood. Therefore, eating a high quantity of starch results in a high level of glucose in the human blood, however, in the case of consuming resistant starch which is immune to digestion, there is a reduction in the glucose in the blood because the starch is not broken dow thereby reducing the risks of some blood diseases that might arise due to excess glucose in the blood ( Olawoye et al., 2020b ).…”
Section: Classification Of Polysaccharidesmentioning
confidence: 99%
“…In healthy humans, resistant starch is starch as well as degrading products of starch, which are not digestible in their small intestine by enzymes ( Olawoye et al., 2020a ; Olawoye et al., 2020b ). Several foods containing carbohydrates in different proportions have resistant starch.…”
Section: Dietary Fibrementioning
confidence: 99%
“… Akintunde et al. (2015) and Olawoye et al. (2020) also reported the superiority of ANN over RSM when optimizing the extraction of oil from Bauhinia monandra seed and cardaba starch respectively.…”
Section: Resultsmentioning
confidence: 96%
“…This result was also supported by the parity plot between the predicted and experimental values. Akintunde et al (2015) and Olawoye et al (2020) also reported the superiority of ANN over RSM when optimizing the extraction of oil from Bauhinia monandra seed and cardaba starch respectively.…”
Section: Comparison Between Rsm and Ann Predicted Valuesmentioning
confidence: 96%
“…The application of the cooking banana is limited due to its high perishability when ripe and unlike dessert banana, it found no usage after ripening. Due to this, it had found application in the production of complementary food (Ayo-Omogie & Ogunsakin, 2013) as well as functional starch (Olawoye et al, 2020a;Olawoye et al, 2020c). However, because the cooking banana contains no gluten, it serves as good raw material in the production of gluten-free products.…”
Section: Introductionmentioning
confidence: 99%